The TEL/platelet-derived growth factor β receptor (PDGFβR) fusion in chronic myelomonocytic leukemia is a transforming protein that self-associates and activates PDGFβR kinase-dependent signaling pathways - Carroll, Martin (The National Academy of Sciences of the USA, 1996)
The TEL/PDGFβR fusion protein is the product of the t(5;12) translocation in patients with chronic myelomonocytic leukemia. The TEL/PDGFβR is an unusual fusion of a putative transcription factor, TEL, to a receptor tyrosine kinase. The translocation fuses the amino terminus of TEL, containing the helix-loop-helix (HLH) domain, to the transmembrane and cytoplasmic domain of the PDGFβR. We hypothesized that TEL/PDGFβR self-association, mediated by the HLH domain of TEL, would lead to constitutive activation of the PDGFβR tyrosine kinase domain and cellular transformation. Analysis of in vitro-translated TEL/PDGFβR confirmed that the protein self-associated and that self-association was abrogated by deletion of 51 aa within the TEL HLH domain. In vivo, TEL/PDGFβR was detected as a 100-kDa protein that was constitutively phosphorylated on tyrosine and transformed the murine hematopoietic cell line Ba/F3 to interleukin 3 growth factor independence. Transformation of Ba/F3 cells required the HLH domain of TEL and the kinase activity of the PDGFβR portion of the fusion protein. Immunoblotting demonstrated that TEL/PDGFβR associated with multiple signaling molecules known to associate with the activated PDGFβR, including phospholipase C γ1, SHP2, and phosphoinositol-3-kinase. TEL/PDGFβR is a novel transforming protein that self-associates and activates PDGFβR-dependent signaling pathways. Oligomerization of TEL/PDGFβR that is dependent on the TEL HLH domain provides further evidence that the HLH domain, highly conserved among ETS family members, is a self-association motif.